Liquidity analysis of oil companies in the Republic of Serbia - Tanja Janaćković; Maša Georgiev; Marko Janaćković (Anali Ekonomskog fakulteta u Subotici, 2022)
The focus of the paper is liquidity analysis, which is an essential tool of the corporate financial management process. Converting assets, especially working capital, into cash is the primary way for a company to obtain the resources it needs to pay its current liabilities. The aim of the research is to look at the movement of current, quick and cash liquidity indicators, their comparative analysis, as well as differences in the level of liquidity for the period 2011-2020 on the example of certain oil companies in the Republic of Serbia. Ratio analysis based on their official financial statements was used to measure the liquidity of selected companies (NIS, OMV and LUKOIL), while the one-way ANOVA test was used to test hypotheses. The research results show that there is a statistically significant difference in the level of current liquidity between NIS and LUKOIL and OMV and LUKOIL, while there is no significant difference between NIS and OMV. There is a statistically significant difference in terms of quick ratios between NIS and LUKOIL, while there is no significant difference between NIS and OMV and OMV and LUKOIL. Observing the cash liquidity indicator, there is no significant difference between these indicators in the companies that are the subject of the research.